2021
DOI: 10.1101/2021.12.14.472691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A reusable benchmark of brain-age prediction from M/EEG resting-state signals

Abstract: Population-level modeling can define quantitative measures of individual aging by applying machine learning to large volumes of brain images. These measures of brain age, obtained from the general population, helped characterize disease severity in neurological populations, improving estimates of diagnosis or prognosis. Magnetoencephalography (MEG) and Electroencephalography (EEG) have the potential to further generalize this approach towards prevention and public health by enabling assessments of brain health… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 130 publications
(179 reference statements)
1
4
0
Order By: Relevance
“…This study explored the feasibility of repurposing EEG-monitoring data from GA for building measures of brain ageing by importing machine learning approaches for brain age prediction originally developed in the laboratory setting. Under propofol anaesthesia, we reached prediction performance comparable to reference studies using research-grade EEG 28,33 . Model comparisons revealed that age-related information was present in spatial activity patterns distributed across the entire power spectrum.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This study explored the feasibility of repurposing EEG-monitoring data from GA for building measures of brain ageing by importing machine learning approaches for brain age prediction originally developed in the laboratory setting. Under propofol anaesthesia, we reached prediction performance comparable to reference studies using research-grade EEG 28,33 . Model comparisons revealed that age-related information was present in spatial activity patterns distributed across the entire power spectrum.…”
Section: Discussionsupporting
confidence: 65%
“…with high-density MEG and EEG 20,32 . Previous studies during anaesthesia have instead focussed on EEG-signatures closely related to anaesthesia monitoring, with particular emphasis on total power and alpha power 6,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the Riemannian Geometry of Symmetric Positive Definite matrices has been widely used for Brain-Computer Interface applications (Barachant et al, 2013;Yger et al, 2017). Recently, in a seminal series of papers, (Sabbagh et al, 2020;Engemann et al, 2021) showed the superiority of HR DPs to predict brain age with MEEG/EEG. Our work differs from these previous applications in two essential aspects.…”
Section: Validation Of the Harmmnqeeg Norms For Classificationmentioning
confidence: 99%